Participatory energy: Research, imaginaries and practices on people' contribute to energy systems in the smart city - Corsini, Filippo; Certomà, Chiara; Dyer, Mark; Frey, Marco (Technological forecasting & social change, 2019)
Scholarly research on smart cities already signalled that citizens' engagement is a fundamental requisite for the achievement of a sustainable and inclusive urban development. Accordingly, transition towards a fossil fuel free future is not to be understood as a matter of techno-economic innovation but as a process in which the ‘social’ and the ‘technical’ are inextricably intertwined, and technologies co-evolve with programmes of governing. Research findings from a recent bibliometric study reveal a very different picture where city dwellers are rarely the subject of research into future energy plans for transition towards a fossil future free future. Instead the research publications tend to concentrate on technological innovation for energy production and consumption. The findings are a concern given that the transition towards a fossil fuel free future will have a greater likelihood of success with public engagement and public acceptance. The paper explores the current transformation of sociotechnical imaginaries towards a more participatory idea of smart cities that emerge from real-world practices; and the resistances and resiliencies to this transformation in research domain. We discuss the evidences emerging from the research on communities energy against the literature on smart energy system. •Public participation is often related to the lack of trust and transparency.•Tools for customized engagement are needed for imagining social participation.•Energy communities' provide useful inputs to transform smart city in city of people.